270OImatinib induced toxicity and its influence on cytogenetic and molecular response in newly diagnosed patients with chronic myeloid leukemia. (24th November 2019) - Natarajan, H; Kumar, L; Bakhshi, S; Sharma, A; Velpandian, T; Kabra, M; Gogia, A; Biswas, N R; Gupta, Y K
Abstract: Background: Incidence of imatinib-induced toxicity and its influence on clinical outcomes in Indian patients with CML is not well-studied. We investigated the influence of imatinib-induced toxicity on therapeutic outcomes in newly diagnosed patients with CML. We also studied the effect of drug levels on imatinib-induced hematological toxicity. Methods: Two hundred and fifty newly diagnosed patients with chronic-phase CML, started on imatinib therapy, were enrolled and followed-up for 24 months. Toxicity due to imatinib were assessed and graded as per CTCAE. Cytogenetic and molecular responses were assessed by conventional bone-marrow cytogenetics and qRTPCR using international scale, respectively, based on which patients were categorized as imatinib responders and non-responders. Imatinib trough levels were measured using LC-MS/MS. Multivariate analysis was done to find the influence of various covariates on imatinib response. Results: A total of 719 adverse reactions due to imatinib occurred among 250 enrolled patients. Hematological toxicity was the most common imatinib-induced toxicity and its incidence was significantly higher in non-responders than responders (65% vs. 35%; P < 0.001). Patients with thrombocytopenia [RR = 1.768; 95%CI (1.357, 2.302); P < 0.001] and neutropenia [RR = 1.654; 95%CI (1.322, 2.070); P < 0.001] were at high risk of imatinib failure. Patients without any hematological toxicity were at lower risk for failure of imatinib therapy [RR = 0.520; 95%CI (0.388, 0.698); P < 0.001]. Although patients with hematological toxicity had higher imatinib levels than those without (2039.1±1361.6 vs. 1833.8±1335.3 ng/mL), the difference was not statistically significant [mean difference 205.2; 95% CI (590.4, -180); P = 0.295]. Hematological toxicity requiring dose interruption or reduction emerged as an independent factor predicting cytogenetic and molecular response to imatinib in multivariate analysis. Conclusions: Imatinib induced hematological toxicities significantly influence cytogenetic and molecular response in patients with CML. Active monitoring and prompt management of imatinib induced adverse events is indispensable to achieve optimal therapeutic outcomes. Clinical trial identification: Not Applicable. Editorial acknowledgement: Not Applicable. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.